2007
DOI: 10.1111/j.1365-2125.2007.02914.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics–pharmacodynamics of alemtuzumab (Campath®) in patients with chronic lymphocytic leukaemia and its link to treatment response

Abstract: AimsTo characterize alemtuzumab pharmacokinetics and its exposure-response relationship with white blood cell (WBC) count in patients with B-cell chronic lymphocytic leukaemia (CLL). MethodsNonlinear mixed effects models were used to characterize plasma concentration-time data and WBC count-time data from 67 patients. Logistic regression was used to relate summary measures of drug exposure to tumour response. ResultsAlemtuzumab pharmacokinetics were best characterized by a two-compartment model with nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 26 publications
5
102
2
Order By: Relevance
“…Rarely does a combined linear and non-linear process describe the elimination of antibodies (Kuester et al, 2008). Values of the final parameters were similar to those reported for other antibodies, with regard to CL from the central compartment and Q, V1 and V2 (Kovarik et al, 2001;Bruno et al, 2005;Ng et al, 2006;Dartois et al, 2007;Mould et al, 2007;Kuester et al, 2008;Lu et al, 2008). This indicates that the HuHMFG1 antibody, similar to other therapeutic antibodies, is mainly distributed in the serum.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Rarely does a combined linear and non-linear process describe the elimination of antibodies (Kuester et al, 2008). Values of the final parameters were similar to those reported for other antibodies, with regard to CL from the central compartment and Q, V1 and V2 (Kovarik et al, 2001;Bruno et al, 2005;Ng et al, 2006;Dartois et al, 2007;Mould et al, 2007;Kuester et al, 2008;Lu et al, 2008). This indicates that the HuHMFG1 antibody, similar to other therapeutic antibodies, is mainly distributed in the serum.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, a structural two-compartmental model is commonly reported to describe the behaviour of antibodies. In these models, the associated elimination is mainly linear (Kovarik et al, 2001;Bruno et al, 2005;Ng et al, 2006;Dartois et al, 2007) and less frequently non-linear (Mould et al, 1999(Mould et al, , 2007. Rarely does a combined linear and non-linear process describe the elimination of antibodies (Kuester et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using an improved pharmacokinetics model to achieve adequate but not excessive drug exposure should optimise alemtuzumab therapy (and probably that of other MoAbs). 16,17 On the basis of the classic schedule, patients undergoing intravenous alemtuzumab therapy receive a theoretical total of 1080 mg, divided into individual doses of 30 mg each.…”
Section: Low-dose Sc Alemtuzumab In Refractory Cllmentioning
confidence: 99%
“…Estimates for the volume of the central (V 1 ) and peripheral (V 2 ) compartments were quite similar for the different mAbs with the exception of alemtuzumab. Compared to other mAbs, alemtuzumab not only had a much larger V 1 and V 2 (11.3 L and 41.5 L, respectively), but between-subject variability in both of these parameters was also larger (84 %CV and 179 %CV, respectively) (23). It is uncertain as to why these population parameter estimates for alemtuzumab are in stark contrast to what was observed for many of the other therapeutic mAbs.…”
Section: Antibody Distributioncontrasting
confidence: 47%
“…Similarly, a population PK/PD analysis in patients with B-cell chronic lymphocytic leukemia found that alemtuzumab exhibited nonlinear clearance attributable to saturation of target-mediated clearance mechanisms (23). The only covariate found to influence the PK of alemtuzumab was white blood cell (WBC) count, which was a strong positive predictor of V max .…”
Section: Receptor Number and Disease-related Factorsmentioning
confidence: 99%